THE PATTERN OF TRAUMATIC HEAD INJURY AT FAISALABAD - Nazar Hussain; Wakeel Ahmad; Akmal Hussain (Journal of University Medical & Dental College, 2015)
ABSTRACT 0BJECTIVE: To study the pattern of traumatic head injury at Faisalabad. PLACE AND DURATION: Neurosurgery Department, Allied Hospital, Faisalabad.From 1.2.2014 to 31.4.2014 . MATERIAL AND METHODS: Two hundreds and ﬁfty patients were recieved at Emergency Department, Allied Hospital Faisalabad during three months .They were assessed and managed. CT Scan was done according to WHO guide lines for head injury patients. RESULTS: Among 250 patients, Male to Female ratio was 7:2 and 72% of patients had met road trafﬁc accident .The other causes include fall, mechanical trauma, hit by animal, etc. Brain contusion was the most common injury observed in this study. Good outcome was found in 58.8% patients and there was 17% mortality at 12 months of follow up. CONCLUSION: Traumatic brain injury has very devastating effect. It has a similar pattern in Faisalabad as in Lahore.